Evaluating abdominal core muscle fatigue: assessment of the validity and reliability of the prone bridging test - De Blaiser, C.; De Ridder, R.; Willems, T.; Danneels, L.; Vanden Bossche, L.; Palmans, T.; Roosen, P. (Scandinavian Journal of Medicine & Science in Sports, 2018)
The aims of present study were to research the amplitude and median frequency characteristics of selected abdominal, back and hip muscles of healthy subjects during a prone bridging endurance test, based on surface electromyography (sEMG), (1) to determine if the prone bridging test is a valid field test to measure abdominal muscle fatigue, and (2) to evaluate if the current method of administrating the prone bridging test is reliable. Thirty healthy subjects participated in this experiment. The sEMG activity of seven abdominal, back and hip muscles was bilaterally measured. Normalized median frequencies were computed from the EMG power spectra. The prone bridging tests were repeated on separate days to evaluate inter- and intra-tester reliability. Significant differences in normalized median frequency slope (NMFslope) values between several abdominal, back and hip muscles could be demonstrated. Moderate to high correlation coefficients were shown between NMFslope values and endurance time. Multiple backward linear regression revealed that the test endurance time could only be significantly predicted by the NMFslope of the rectus abdominis. Statistical analysis showed excellent reliability (ICC = 0.87-0.89). The findings of the present study support the validity and reliability of the prone bridging test for evaluating abdominal muscle fatigue